Morphological and phenotypical characteristics of human osteoblasts after short-term space mission - Abd Manaf, Ali; M Yu, Kapitonova; S L, Kuznetsov (2014)
Morphological and phenotypical signs of cultured readaptation osteoblasts were studied after a short-term space mission. The ultrastructure and phenotype of human osteoblasts after Soyuz TMA-11 space flight (2007) were evaluated by scanning electron microscopy, laser confocal microscopy, and ELISA. The morphofunctional changes in cell cultures persisted after 12 passages. Osteoblasts retained the drastic changes in their shape and size, contour deformation, disorganization of the microtubular network, redistribution of organelles and specialized structures of the plasmalemma in comparison with the ground control cells. On the other hand, the expression of osteoprotegerin and osteocalcin (bone metabolism markers) increased; the expression of bone resorption markers ICAM-1 and IL-6 also increased, while the expression of VCAM-1 decreased. Hence, space flight led to the development of persistent shifts in cultured osteoblasts indicating injuries to the cytoskeleton and the phenotype changes, indicating modulation of bone metabolism biomarkers.